Small forms of Blastocystis hominis - Rajah, S.; Kumar, Suresh; Vennila, G.D.; Khairul Anuar, A.; Saminathan, R. (Faculty of Medicine, University of Malaya, 2002)
Unusually small forms of Blastocystis hominis were found in the stools of Indonesian immigrants. The size of the parasites seen in faecal samples of the Indonesian isolates were 3 ' 5 mm whereas larger vacuolar forms measuring 10 ' 15 mm were seen Malaysian and Bangladeshi isolates. These small forms showed a distinct growth profile with an optimum parasite yield as high as 11.7 ' 105 when cultured in Jone's medium compared to yield of 3.9 ' 105 and 0.5 ' 105 for Malaysian and Bangladeshi isolates respectively. The unusually small forms of Blastocystis, unlike the other isolates, was found to grow in cultures at 37'C even after being kept at room temperature for as long as 9 days.